Plasma Oxytocin and Vasopressin Levels in Young and Older Men and Women: Functional Relationships with Attachment and Cognition - Plasencia, Gabriela (Psychoneuroendocrinology, 2019)
A growing literature associates the neuropeptides oxytocin (OT) and arginine vasopressin (AVP) with affiliative and cognitive outcomes. The majority of this work in humans, however, considers these neuropeptides separately. Also, despite evidence that OT and AVP interact with gonadal hormones, still warranted is an examination of sex and age variations in endogenous neuropeptide levels, their interrelations, and their functional relationships with attachment and cognition in humans. This study measured endogenous plasma OT and AVP levels in generally healthy young (18–31 years) and older (63–81 years) men and women to (i) determine levels of and interrelations between OT and AVP; (ii) explore functional relationships with self-reported attachment (attachment anxiety and avoidance) and performance-based cognition (processing speed, verbal memory); and (iii) identify variations in these effects by sex and age. We observed sex- and age-differential patterns of results: Women had higher plasma OT levels than men and older adults had higher plasma AVP levels than young adults. The two neuropeptides were highly negatively intercorrelated across all groups. Functionally, higher AVP levels were associated with greater attachment anxiety and higher OT and lower AVP levels were associated with faster sensorimotor processing speed, with sex and age moderating these effects. This integrated approach identifies variations in endogenous peripheral neuropeptide levels in humans, supporting their sex- and age-specific role as “difference makers” in attachment and cognition.